2014
DOI: 10.1007/s13277-014-2346-6
|View full text |Cite
|
Sign up to set email alerts
|

NBS1 Glu185Gln polymorphism and susceptibility to urinary system cancer: a meta-analysis

Abstract: A number of studies have investigated the association between the NBS1 Glu185Gln (rs1805794, 8360 G>C) polymorphism and risk for urinary system cancer including bladder cancer, prostate cancer, and renal cell cancer; however, the findings are conflicting. We conducted a meta-analysis focusing on eight published studies with 3,542 cases and 4,210 controls to derive a more precise evaluation of the relationship between the NBS1 Glu185Gln polymorphism and urinary system cancer susceptibility. Overall, the NBS1 Gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 36 publications
2
19
0
Order By: Relevance
“…NBS1 rs1805794 polymorphism, which has frequently been studied, is associated with risks of breast cancer [ 27 ], cervix carcinoma [ 31 ], nasopharyngeal carcinoma [ 20 ], and bladder cancer [ 32 ]. Moreover, functional studies have demonstrated that the rs1805794G > C is functional and could recede the DNA repair capacity of NBS1 [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…NBS1 rs1805794 polymorphism, which has frequently been studied, is associated with risks of breast cancer [ 27 ], cervix carcinoma [ 31 ], nasopharyngeal carcinoma [ 20 ], and bladder cancer [ 32 ]. Moreover, functional studies have demonstrated that the rs1805794G > C is functional and could recede the DNA repair capacity of NBS1 [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…These tumor histotypes retain their morphologic features, being often referred to as differentiated thyroid carcinoma (DTC) [3,4]. The best-established modifiable risk factor for DTC is IR exposure during childhood and adolescence (radioiodines including 131 I, X-radiation, γ-radiation) [2][3][4][5] and the standard treatment consists of surgical resection (total or near-total thyroidectomy) accompanied by post-thyroidectomy radioiodine (RAI) therapy and TSH suppression [3,4]. The majority of DTC cases is indolent in nature, iodine-avid, and responds favorably to standard therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The widespread use of RAI therapy in the management of DTC relies on the ability of 131 I to be preferentially taken up and concentrated in normal or neoplastic thyroid follicular cells, taking advantage of these cells' specialized mechanism for iodide uptake and accumulation [3,6,7]. Thyrocyte-accumulated 131 I undergoes [β and γ] decay and releases high-energy electrons that inflict devastating DNA damage locally. Thyroid cell death through radiation cytotoxicity ensues, allowing for the ablation of remnant normal thyroid tissue and the eradication of any residual tumor foci [3,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…p.E185Q; rs1805794 and c.2265 + 541G > C; rs2735383) have also been reported to be associated with risks for several cancer types. Recent meta-analyses for rs1805794 have, however, shown that this variant does not associate with breast cancer risk13141516, while associations with lung cancer and urinary system cancer are still inconclusive13161718. The functional variant rs2735383, localized in in the 3′ UTR of NBS1 , has been shown to modulate the binding ability of microRNA-629 in lung cancer cells and microRNA-509-5p in colorectal cancer cells, affect NBS1 transcriptional activity and decrease NBS1 mRNA and NBS1 protein levels1920.…”
mentioning
confidence: 99%